Conjuntos de bases gaussianas correlacionados não relativístico e relativístico : aplicação em cálculos de constantes espectroscópicas e de propriedades elétricas e magnéticas moleculares - Camiletti, Giuseppi Gava (2009)
Contracted basis set of double zeta (DZ) quality for the atoms from K to Kr is presented. It was determined from fully-optimized basis set of primitive Gaussian-type functions generated in atomic Hartree-Fock calculations. Sets of Gaussian polarization functions optimized at the Mfller-Plesset second-order level were added to the DZ basis set. This extends earlier work on segmented contracted DZ basis set for atoms H-Ar. From this set, using the BP86 non-hybrid and B3LYP hybrid functionals, dissociation energy, geometric parameters, harmonic vibrational frequency, and electric dipole moment of a set of molecules were calculated and compared with results obtained with other basis sets and with experimental data reported in the literature. In addition, 57Fe and 77Se nuclear magnetic resonance chemical shifts in Fe(C5H5)2, H2Se, and CSe2 were calculated using density functional theory and gauge-including atomic orbitals and, then, compared with theoretical and experimental values previously published in the literature. Except for chemical shift, one verifies that our results give the best agreement with experimental and benchmark values. Augmented Gaussian basis sets of double and triple zeta valence qualities plus polarization functions for the atoms K and from Sc to Zn are also presented. They were generated from the all-electron unaugmented sets by addition of diffuse functions (s, p, d, f, and g symmetries), that were optimized for the anion ground states. From these sets, HartreeFock, second-order Mfller-Plesset perturbation theory, and density functional theory electric dipole moment and dipole polarizability calculations for a sample of molecules were carried out. Finally, Douglas-Kroll-Hess (DKH) contracted Gaussian basis sets of double, triple, and quadruple zeta valence qualities plus polarization functions (XZP, X=D, T, and Q, respectively) for the atoms H, Li, Be, Na, and Mg and DZP and TZP for K-Zn are presented. xv They have been determined from the corresponding non-relativistic basis sets generated previously by Jorge et al. We have recontracted the original XZP basis sets, i.e., the values of the contraction coefficients were reoptimized using the relativistic DKH Hamiltonian. The scalar relativistic effect at the coupled-cluster level of theory on the ionization energy of some atoms and dissociation energy and geometric parameters for a sample of molecules is discussed. All results obtained in this work were compared with theoretical and experimental values available in the literature